2017
DOI: 10.1039/c7nr01186e
|View full text |Cite
|
Sign up to set email alerts
|

Air and thermally stable perovskite solar cells with CVD-graphene as the blocking layer

Abstract: The poor air and thermal stability of organic-inorganic halide perovskite solar cells have hindered their real applications. Here we report the insertion of a chemical vapor deposited graphene between the Au electrode and spiro-OMeTAD in planar perovskite solar cells to block the diffusion of air and Au into the perovskite layer, where the single layer graphene is transferred into the devices by a simple laminated process. After ageing in 45% humidity air for 96 h or thermal annealing at 80 °C for 12 h, more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…Figure a–d shows scanning electron microscopy (SEM) images of the perovskite films without and with (wo/w) TPFPB passivation. Remarkably, a significant increase in both the water contact angle and grain size of the perovskite film w TPFPB passivation was observed, which is better for the stability of PSCs due to the improved hydrophobicity and reduced density of grain boundaries . Some “bright crystals” on the surface of the perovskite film wo TPFPB passivation are δ‐phase perovskite rather than PbI 2 , as confirmed by the EDX results (Figure S2, Supporting Information), which is consistent with the results reported recently by Yuan et al The Pb, I, and N of the perovskite are tracked at points A (bright crystal) and B.…”
Section: Resultssupporting
confidence: 90%
“…Figure a–d shows scanning electron microscopy (SEM) images of the perovskite films without and with (wo/w) TPFPB passivation. Remarkably, a significant increase in both the water contact angle and grain size of the perovskite film w TPFPB passivation was observed, which is better for the stability of PSCs due to the improved hydrophobicity and reduced density of grain boundaries . Some “bright crystals” on the surface of the perovskite film wo TPFPB passivation are δ‐phase perovskite rather than PbI 2 , as confirmed by the EDX results (Figure S2, Supporting Information), which is consistent with the results reported recently by Yuan et al The Pb, I, and N of the perovskite are tracked at points A (bright crystal) and B.…”
Section: Resultssupporting
confidence: 90%
“…Obviously, when the CsAc concentration is 1.2 mol%, the average grain size reaches the maximum value, which is consistent with the XRD results (Figure a). Remarkably, the average grain size of the perovskite films (1.39 μm) with 1.2 mol% CsAc alloying is increased by almost three times compared with the control samples (0.457 μm), which is benefit for the stability of perovskite film due to the reduced density of grain boundaries …”
Section: Resultsmentioning
confidence: 92%
“…Further, electrochemical impedance spectroscopy (EIS) measurements are performed to provide insight into the charge carrier recombination in the CsPbI 2 Br PSCs, and the corresponding Nyquist plots and equivalent circuit model are presented in Figure 3f;38 the fitting parameters are listed in Table S4 in the Supporting Information. It is found that the optimized devices exhibit lower series resistance ( R s ) and much higher recombination resistance ( R rec ) than the control device 39.…”
Section: Resultsmentioning
confidence: 99%